Polymers enhanced magnetite by one-step sol-gel auto-combustion for magnetic hyperthermia application - Nwabunwanne, Christian; Aisida, Samson O.; Alshoaibi, Adil; Almulhem, Najla; IsIam, Shumaila; Ezema, Fabian I. (SPRINGER HEIDELBERG, 2026)
Magnetic hyperthermia therapy using magnetite (Fe3O4) has attracted considerable attention due to its promising anti-cancer strategy, as well as a precise spatial controllability and immune-activating effects either as a single treatment or as an adjuvant with chemotherapy, hydrogen therapy and immunotherapy. However, the clinical application of magnetite is limited owing to its uncontrollable motion and high reactivity in physiological environments. To address these drawbacks, we have developed polyethylene glycol (PEG), chitosan (CS) and alginate (Alg) coated Fe3O4 nanoparticles via the sol-gel autocombustion method. The phase-purity cubic spinel structures of the samples were confirmed by XRD analysis. SEM observations revealed polymer-dependent morphological evolution and a slight particle size increase. The Optical studies exhibited tunable bandgap energies following polymer coating, reflecting strong interfacial interactions between the Fe3O4 core and organic shells. Magnetic properties measurements showed superparamagnetic behavior at room temperature, with improved saturation magnetization after polymer surface modification. Polymer encapsulation influenced the physicochemical properties of the samples. These changes significantly enhanced magnetic heating efficiency. The specific absorption rate (SAR) increased from 219 W g(-)& sup1; for pristine (Fe3O4) to 787 W g(-)& sup1; for PEG/Fe3O4, as well as high intrinsic loss power (ILP) values, enabling rapid temperature elevation within the therapeutic hyperthermia range. Hemolysis studies revealed dose-dependent behavior; however, the elevated SAR and ILP values of polymer-coated samples suggest that lower clinical doses mitigate blood compatibility concerns. Overall, polymer-engineered Fe3O4 nanoparticles, particularly PEG-coated systems, demonstrate an optimal balance between magnetic heating performance and biocompatibility, highlighting their strong potential for safe and effective clinical magnetic hyperthermia. [GRAPHICS]
Keywords: Nanoparticles; Magnetite; Polymers; Sol-gel; Hyperthermia; IRON-OXIDE NANOPARTICLES; ZINC FERRITE; DRUG; Materials Science; Physics